2017
DOI: 10.1016/j.dnarep.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Probing the activity of NTHL1 orthologs by targeting conserved amino acid residues

Abstract: The base excision repair DNA glycosylases, EcoNth and hNTHL1, are homologous, with reported overlapping yet different substrate specificities. The catalytic amino acid residues are known and are identical between the two enzymes although the exact structures of the substrate binding pockets remain to be determined. We sought to explore the sequence basis of substrate differences using a phylogeny-based design of site-directed mutations. Mutations were made for each enzyme in the vicinity of the active site and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In the open state, the strictly conserved catalytic residues, Lys 220 and Asp 239, which are located ∼5 Å apart in the bacterial enzymes, are found ∼23 Å apart (Figure 1 ). Therefore, hNTHL1 must undergo a conformational change in order for catalysis to occur ( 17 , 19 , 59–61 ). This finding was unexpected as the bacterial homologs were captured in a similar closed conformation, in the presence and absence of DNA (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the open state, the strictly conserved catalytic residues, Lys 220 and Asp 239, which are located ∼5 Å apart in the bacterial enzymes, are found ∼23 Å apart (Figure 1 ). Therefore, hNTHL1 must undergo a conformational change in order for catalysis to occur ( 17 , 19 , 59–61 ). This finding was unexpected as the bacterial homologs were captured in a similar closed conformation, in the presence and absence of DNA (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Robey-Bond et al. investigated several residues which were deemed important for catalysis in E. coli and yet had a different amino acid residue at the analogous position in mammalian NTHL1 ( 19 ), including Asn279, Gly280, and Gln287 ( 19 ). Our crystal structure of hNTHL1 shows that Asn 279 and Gly 280 are located near linker 2, with the former contacting the backbone carbonyl of Ala 137 in that linker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the open state, the strictly conserved catalytic residues, Lys 220 and Asp 239, which are located ~5 Å apart in the bacterial enzymes, are found ~23 Å apart (Figure 1). Therefore, hNTHL1 must undergo a conformational change in order for catalysis to occur (17,19,(60)(61)(62). This finding was unexpected as the bacterial homologs were captured in a similar closed conformation, in the presence and absence of DNA (Figure 1).…”
Section: The Flexible Linker Is Necessary For the Open Statementioning
confidence: 94%
“…Nth is a bifunctional DNA glycosylase with a marked preference for oxidized pyrimidine substrates (16). While both Escherichia coli Nth (EcoNth) and human NTHL1 (hNTHL1) glycosylases display a preference for excising lesions opposite G, the human enzyme is slower than the bacterial enzyme on most substrates (17)(18)(19). The first bacterial Nth crystal structure, EcoNth, revealed that the enzyme consists of two globular α -helical domains, a six-helical bundle domain and a [4Fe4S] cluster domain.…”
Section: Introductionmentioning
confidence: 99%